Effect of Levels of Nitrogen on the Growth and Yield of Sesame (Sesamum indicum L.) Cultivars (Journal of the Bangladesh Agricultural University, 2024)
An experiment was conducted at Central Farm, Farm Management Section of Bangladesh Agricultural University, Mymensingh during March to June 2018 to find out the effect of levels of nitrogen on the growth and yield of sesame (Sesamum indicum L.). The experiment comprised five cultivars of sesame viz. BARI Til-3, BARI Til-4, Binatil-1, Binatil-2, Binatil-3 and four levels of nitrogen in the form of urea viz. 0, 40, 80 and 120 kg urea ha-1. The experiment was laid out in a randomized complete block design with three replications. Growth, yield components and yield of sesame were significantly influenced by cultivars, levels of nitrogen and their interaction. At vegetative stage, the tallest plant and highest dry matter were observed in BARI Til-4 at 50 days after sowing (DAS) and 70 DAS, respectively. Application of 120 kg urea ha-1 (150 % of recommended dose) produced the tallest plant and highest dry matter at 70 DAS. Interaction of cultivar and level of nitrogen did not exert any significant effect on plant height and dry matter production at different days after sowing. Plant height, number of capsule plant-1, seeds capsule-1, 1000-seed weight, seed yield and biological yield were varied significantly with increasing urea level up to 80 kg ha-1 whereas stover yield was increased up to 120 kg urea ha-1 but branches plant-1 and harvest index showed non-significant variation. From the interaction it is observed that BARI Til-4 fertilized with 80 kg urea ha-1 gave the highest plant height (80.49 cm), highest number of branches plant-1 (3.20), highest number of capsules plant-1 (35.30), maximum seed yield (2.23 t ha-1) and highest harvest index (18.82%). The highest stover yield (10.34 t ha-1) was found in BARI Til-4 fertilized with 120 kg urea ha-1. Therefore, BARI Til-4 fertilized with 80 kg urea ha-1 was found to be promising practice in respect of growth and yield of sesame.   J Bangladesh Agril Univ 18(4): 949–955, 2020